Polyurethane shape memory polymer: structure characterization and estimation of energy storage and dissipation during the tension process - Staszczak, Maria; Gradys, Arkadiusz; Golasiński, Karol; Pieczyska, Elżbieta A. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Shape memory polymers (SMP) are new multifunctional materials raising increasing interest in various functional applications. Among them, polyurethane shape memory polymers (PU-SMP) are particularly attractive due to their combination of shape memory, high strength and biocompatible properties. Developing new applications for PU-SMP requires comprehensive research on their characteristics. This work involved investigating the structure and mechanical behavior as well as characterizing the energy storage and dissipation of a thermoplastic PU-SMP with a glass transition temperature (Tg) of 25_C during tensile loading-unloading. The process of energy storage and dissipation in the PU-SMP was investigated based on the stress-strain curves recorded by a quasi-static testing machine and the temperature changes, accompanying the deformation process, obtained by using a fast and sensitive infrared camera. The results showed that the thermomechanical behavior of the examined PU-SMP depends significantly on the strain rate. At a higher strain rate, there are higher stress and related temperature changes, which lead to greater energy dissipation. However, the energy storage values estimated during the deformation process turned out to be not significant, indicating that the work supplied to the PU-SMP structure during loading is mainly converted into heat. It should also be noted that the structural investigation revealed no crystalline phase in the investigated PU-SMP.